Alterations in Serum Myostatin Levels via Swimming Exercise in High Fructose Mediated Metabolic Syndrome Model - Karaman, Muhammed Emre; Arslan, Cengiz; Gursu, Mehmet Ferit; Arat, Zelal; Turkoglu, Furkan (Sciencedomain Int, 2021)
Aims: Metabolic syndrome is a table of abdominal diseases characterized by insulin resistance, obesity, dyslipidemia, and hypertension, and it is a serious risk factor for the development of cardiovascular diseases. The purpose of this study was to understand how metabolic syndrome causes a change in myostatin levels, and to understand if swimming exercise have protective and therapeutic effects in fructose mediated metabolic syndrome model by regulating serum myostatin level. Methodology: A total of 21 Sprague Dawley male rats were used in the study. Metabolic syndrome was induced by adding 30% fructose into drinking water for 5 weeks The rats (6-8 weeks old, weighing 200-250 g) were randomly divided into 3 groups as 7 rats in each cage. Swimming exercises were applied three days a week for six weeks. On exercise days, rats were exercised for 20 minutes in a day. Blood was collected from all animals in aprotinin tubes to be used in the necessary analysis with decapitation. Serum samples obtained after centrifugation were kept at -80 degrees C until the assay were performed. In serum samples, myostatin was measured by ELISA method. Results: There was a statistically significant difference resulting from G2, which had the highest value in glucose and triglyceride levels between groups. G2 had the lowest HDL levels. Myostatin levels were significantly higher in G2 compared to other groups. Conclusion: Moderate swimming exercises are protective and therapeutic in preventing chronic diseases such as diabetes, obesity and metabolic syndrome. In line with these results, it can be said that swimming exercise is a therapeutic practice that regulates impaired fasting serum glucose, increased TG levels and decreased HDL levels and downregulates serum myostatin levels.
Keywords: Metabolic syndrome; swimming exercise; myostatin (MSTN); lipid profile; myokine